Vers une transition énergétique des pays émergents : quelles politiques d’incitation aux énergies renouvelables dans le secteur électrique en Argentine et au Brésil ? - Germán Bersalli; Jean-Christophe Simon (Développement Durable et Territoires)
In South America a possible energy transition in the electrical sector is currently facing both major challenges and opportunities : they are strongly determined by the domestic contexts of countries’ development. National priorities such as access to electricity for households and security of supply are paramount but a new dimension of energy policy derives from the increasing importance of the climate change issues. Sustainability, as a dynamic concept, aims at finding a balance between goals that can complement or sometimes contradict each other. Over the past decade, several countries have actively promoted new renewable sources of electricity, through various incentive mechanisms : tradable quota system, feed-in tariff, bidding, etc. The results differ according to countries and two cases, Argentina and Brazil, present thought-provoking experiences. This paper first explores the energy transition notion and its implication for socio economic development in South American countries. Then, different objectives and possible negative effects of renewable energy development are analysed. Finally, the article focuses on renewable electricity policies in two selected countries, their scope, tools and effectiveness.